Research on Energy System Planning of Data Center Based on Hydrogen-Electric Coupling - Yiming KE; Hongyu TANG; Wei LIU (南方能源建设, 2023)
[Introduction] Scientific planning of data center energy system can save energy and reduce carbon, and then orderly realize "dual control" for the total energy consumption and energy intensity as well as "carbon peak and neutrality" goals. However, the existing researches on planning mainly focus on pure electrochemical energy storage, without considering the new storage mode of hydrogen and electricity coupling; few studies establish planning models by integrating sources and loads under the guidance of pure green development. [Method] Based on the concept of green energy supply and hydrogen-electric coupling, the storage, conversion and balance of electricity, heat and cold energy streams were analyzed. Further, from the dimensions of reducing costs and reducing external energy dependence, the optimal configuration model of the data center energy system that takes into account photovoltaic power generation, hydrogen energy storage and electrochemical energy storage was constructed, and was verified by case study. [Result] The case analysis shows that compared with the pure electrochemical energy storage, the planning scheme considering the hydrogen-electric coupling storage has lower costs and lower dependence on external energy, and the proposed model can well reflect the reality. [Conclusion] The research results of this article not only provide quantitative guidance for energy system planning of data centers, but also help data centers achieve energy conservation and carbon reduction, ensuring their green and sustainable development.